A national survey on the impact of the COVID-19 pandemic upon burnout and career satisfaction among neurosurgery residents. (October 2020) - Khalafallah, Adham M.; Lam, Shravika; Gami, Abhishek; Dornbos, David L.; Sivakumar, Walavan; Johnson, Jeremiah N.; Mukherjee, Debraj
Highlights: U.S. neurosurgery residents report moderate burnout during the COVID-19 pandemic. Neurosurgery residents report uncertainty about future healthcare reform & earnings. The COVID-19 pandemic may impair residents' achievement of surgical milestones. Burnout is associated with altered rotation or vacation schedules and lower PGY. Career satisfaction is associated with delivery of neurosurgical patient care. Abstract: The coronavirus disease 2019 (COVID-19) pandemic has posed significant changes to resident education and workflow. However, the impact of the pandemic on U.S. neurosurgery residents has not been well characterized. We investigated the impact of the COVID-19 pandemic on U.S. neurosurgery resident workflow, burnout, and career satisfaction. In 2020, a survey evaluating factors related to career satisfaction and burnout was emailed to 1, 374 American Association of Neurological Surgeons (AANS) residents. Bivariate and multivariate (logistic) analyses were performed to characterize predictors of burnout and career satisfaction. 167 survey responses were received, with a response rate (12.2%) comparable to that of similar studies. Exclusion of incomplete responses yielded 111 complete responses. Most respondents were male (65.8%) and White (75.7%). Residents reported fewer work hours (67.6%) and concern that COVID-19 would impair their achievement of surgical milestones (65.8%). Burnout was identified in 29 (26.1%) respondents and career satisfaction in 82 (73.9%) respondents. In multivariate analysis, burnout was significantly associated with alterations in elective rotation/vacation schedules (p = .013) and the decision to not pursue neurosurgery again if given the choice (p < .001). Higher post-graduate year was associated with less burnout (p = .011). Residents displayed greater career satisfaction when focusing their clinical work upon neurosurgical care (p = .065). Factors related to COVID-19 have contributed to workflow changes among U.S. neurosurgery residents. We report a moderate burnout rate and a paradoxically high career satisfaction rate among neurosurgery residents. Understanding modifiable stressors during the COVID-19 pandemic may help to formulate interventions to mitigate burnout and improve career satisfaction among residents.